A Máramarosszigeti Református Jogakadémia „áttelepülése” Magyarországra - József KEREKES (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The Relocation of the Reformed Law Academy in Máramarossziget to Hungary. The law academy in Máramarossziget, founded in 1837, was shut down in 1854 by Minister of the Interior Bach because of its participation in the Hungarian Revolution of 1848. It reopened its gates to the students only in 1869. The law-academy flourished in the 20th century, having more than 120 students. It received support and sponsorship from the Prime Minister himself. However, the Great War sealed its fate. Two thirds of the whole faculty and most of the students were enrolled in the army. This tragedy was followed by an even greater one: the Spanish flu epidemic. Also, the Russian army ravaged the land, followed by the regime change. After the Peace Dictate, the law academy became part of the Romanian Kingdom’s territory. The faculty accepted the invitation of the town of Hódmezővásár-hely and relocated itself to Hungary in 1921. Unfortunately, because of its unfavourable financial state and the decision of the Reformed Diocese of Tiszántúl, the Minister of Cults and Education closed down the academy for good in 1923. This was the last law academy founded by the church. Its rightful successor became the law academy of Kecskemét, one that was acknowledged nation-wide by the Reformed Church of Hungary.